A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith; Wyse, Dominic (Routledge, 2010)
OCLC: ocn299711187
Keywords: Great Britain; Student teaching; Teachers; Training of

Lusofonia, encruzilhadas culturais, Actas da Conferência sobre Lusofonia - Correia, Ana; Sousa, Ivo (Saint Joseph University Press, 2011)

China-Africa: emerging relations - Sousa, Ivo Carneiro de; Diakite, Ansoumane Douty; Iwaloye, Ojo Olukayode (Saint Joseph Academic Press, 2011)
Meeting Name: China-Africa: New Types of Exchange, Cultural Identity and Emerging Relations in a Globalized World
Keywords: Africa China Congresses; China Africa Congresses; Relations

Os índios potiguara: memória, asilo e poder - Simões, José Manuel (Editora Media XXI, 2013)

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2013)

Managing complex change in school: engaging pedagogy, technology, learning and leadership - Garcia, Alejandro Salcedo; Morrison, Keith (Routledge, 2014)
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Leadership; Educational change; Educational leadership; Educational technology

The Inner Harbour - Background Document on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour – Policy Recommendations on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

Design Thinking associated with R&D: Process Management and Knowledge Transfer for the Creative Industries - Cerejo, Joana; Barbosa, Álvaro (LAP LAMBERT Academic Publishing, 2014)
The difficult task of innovation is a key facet of Research & Development (R&D) institutions. To Design, innovation is to make the project technically feasible, economically viable, merchandising interesting and emotionally engaging. Design Thinking integrated with R&D organizations can foster the relationship between Universities and new markets. By addressing these topics, this book researches new emerging design methods and provide an overview of Design Thinking tools that can be applied in an early stage of the R&D research process to produce meaningful results. It is taken into account that design, through Design Thinking, extends to the experience that costumers/users have with products/services or even multidimensional experiences, which is a relevant input for R&D innovation development. In fact, the establishment of coherent guidelines for the Design Thinking process is a very complex task, due to its interdisciplinary requirements, that convey many diverse mindsets. The main focus of this book is creating an analysis toolkit that enables non-specialist and specialist users to perform high-quality design solutions.
GSCC: 0001007

Responsible Entrepreneurship. How to Write a Business Plan (Chinese-English Version) - Rothlin, Stephan; Myers, T. A; Thompson, M (University of International Business and Economics Press, 2015)

Historical Space in Macao - Pinheiro, Francisco Vizeu (IACM : Jiangnam University, 2016)

International Business Ethics: Focus on China - Rothlin, Stephan; McCann, Dennis (Springer-Verlag, 2016)
This book addresses an essential need felt by many who seek to promote best business practices in China and East Asia – namely the need for culturally appropriate instructional materials (basic information, case studies and ethical perspectives) that will allow managers and entrepreneurs to understand and embrace the challenge of moral leadership in business. In an era characterized by globalization and the increasing importance of the economies of China, India, Japan and SE Asia, international business ethics must reflect the concerns of the people living and working in this area, the moral and spiritual traditions that have nurtured them and their specific contributions to sustainable development. This book presents twenty important case studies, taken from newsworthy events of the past few years, in which Asians and others have attempted to respond to this challenge. Each case study has been selected and shaped in order to highlight various aspects of doing business in Asia, starting with basic principles and moving on to the specific responsibilities that businesses have towards their various stakeholders. The authors contend that the best way to appreciate the relevance of Asian moral and spiritual traditions is to determine their specific contribution to virtue ethics, where the ancient traditions of both East and West converge in their focus on the qualities of moral leadership that form the basis of best business practice. Exploring the case studies will enable readers to appreciate the continued relevance of these ethical perspectives in Asian business. Best business practice clearly involves learning to do business and playing the game according to the rules; but the necessity of playing by the rules is not likely to become clear until one takes up the path that leads to a virtuous life in business, developing a moral character chiefly based on integrity.

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

De Portugal a Macau: Filosofia e Literatura no Diálogo das Culturas - Natário, Maria Celeste; Espadinha, Maria Antónia (Universidade do Porto, Faculdade de Letras, 2017)

O português dos Tongas de São Tomé. In Oliveira, Márcia Santos Duarte; Araujo, Gabriel Antunes. (orgs.) O português na Africa atlântica - Baxter, A. N. (Humanitas/FAPESP, 2018)

Steps of Greatness: Geopolitics of OBOR, Ed. University of Macau. - Leandro, Francisco José (University of Macau, 2018)

Translation into Portuguese of the work Macau Days - a tri-lingual book (English, Portuguese, Chinese) that includes a series of poetic texts by Brian Castro and artworks by John Young, 2017 in collaboration with the J.M. Coetzee Centre for Creative Practice and the EU Centre for Global Affairs, University of Adelaide, Australia. - Morais, I. (A-A-Publishing, 2018)

Implementing cross-curricular themes - Morrison, Keith (2018)
OCLC: 1015674903

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (IGI Global, 2018)

The Inner Harbour Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2018)

Pekinger Nachtgespräche: Gott und die Welt in China (Nighttalks in Beijing. God and the World in China) - Rothlin, Stephan; Achten, Peter (Fromm Verlag, 2018)

Perspectives on Inclusion - Correia, Ana; Couzens, Donna; Ho, Ka Lee Carrie (University of Saint Joseph, 2019)
In an inclusive education system, educators engage with increasing their understanding of individual differences, especially in regard to learning, and develop and adjust learning and assessment tasks and contexts in ways that make them accessible and appropriate for all students regardless of starting ability levels, interests, learning strengths and weaknesses. In inclusive schools, diverse approaches to learning are valued and all learners are challenged and supported to be successful in their learning goals. Macao has begun the journey to develop an increasingly inclusive education system. This book has been written as the journey is beggining and explores some of the different perspectives twoard inclusion and interpretaions of "inclusive education" within Macao's education systems and the wider community at this time. The main aims of the research presented in this book are to understand the different views and roles of staff in Macao schools and in the wider community. The book raises questions about how inclusion in Macao might unfold and identifies areas where efforts may be needed to progress inclusive education.
Sponsored by Macau Foundation